Synthesis and Spectrophotometric Determination of 7-Hydroxy-4-methyl Coumarin Containing Schiff Base Derivatives with Potential Antimicrobial and Antioxidant Activities - S.V. Satyanarayana, V.; Rakshit, Madhumita; Sivakumar, A. (Asian Journal of Chemistry, 2010)
2-[(4-Methyl-2-oxo-2H-chromen-7-yl)oxy]acetohydrazide (3), aryl/hetero aromatic aldehydes were condensed under reflux temperature for the synthesis of new Schiff base 2-[(4-methyl-2- oxo-2H-chromen-7-yl)oxy]-N'-(substitutedmethylene)acetohydrazides (4a-l) and characterized through IR, 1H NMR and Mass spectral data. The synthesized compounds have been screened for their antimicrobial activity in MIC levels against E. coli, S. aureus and P. aeruginase. The antioxidant activity of Schiff base containing coumarin moiety and its derivatives were investigated using the DPPH radical scavenging method. All these derivatives were subjected to UV-visible analysis and the molar absorptivity (ε) was determined using maximum absorbance at different wavelengths for all the compounds.